Implications and reflections on the 2010 Supreme Court ruling on Canada's AHR Act - Deonandan R; Rahman T (Dove Medical Press, 2011)
Raywat Deonandan, Tarun RahmanInterdisciplinary School of Health Sciences, University of Ottawa, Ottawa, Ontario, CanadaAbstract: In December, 2010, Canada's 6 year old Assisted Human Reproduction Act was successfully challenged in the Supreme Court of Canada. There may be important implications for public health and the evolution of reproductive technologies in this country.Keywords: public health, reproductive medicine, IVF, ART, in vitro fertilization (IVF)